The CAPI effect boosting survey data through mobile technology. (Key indicators for Asia and the Pacific., 2019)
The first part of this publication provides rigorous quantitative evidence on why CAPI is a better alternative to the traditional pen and paper interviewing method, particularly in the context of nationally representative surveys. The second part discusses the benefits of delivering CAPI training to statisticians using the popular massive online open course format. The final part provides a summary of existing CAPI platforms and offers some preliminary advice for NSOs to consider when selecting a CAPI platform for their institution.